Analisis Kesalahan Berbahasa dalam Materi Debat Siswa Kelas X ATPH SMK Negeri 3 Alasa: Penelitian - Sukardi Hulu; Arozatulo Bawamenewi; Lestari Waruwu; Yanida Buulolo (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to identify and describe what pronunciation errors occur in the debate of class X ATPH students of SMK Negeri 3 Alasa. The focus of this study is language errors at the level of phonology, namely pronunciation or speech errors, including pronunciation errors in the form of changes, omissions and additions of phonemes. The research method used is descriptive qualitative with data collection techniques in the form of documentation, observation and interviews. Factors causing student language errors are physical conditions, cognitive abilities, environmental influences, lack of learning motivation, regional language influences, lack of practice, and lack of parental support. The results showed that there were 9 language errors, namely 2 phoneme changes, 4 phoneme deletions and 3 phoneme additions. The findings are expected to be the basis for evaluation and improvement in Indonesian language learning, especially in the development of formal speaking skills in the school environment.